Co-occurring Toxoplasma Infection and Psychotic Symptoms: Case Report - Carla R Marchira; Andrian F Kusumadewi; Patricia Wulandari (Scientia Psychiatrica, 2020)
Introduction: Schizophrenia is a neuropsychiatric disease that is global and is experienced by 1% of the population in the United States and Europe. This study raises awareness of the role of infectious agents in the initiation of psychotic symptoms in schizophrenia. Case presentation: A 20-year-old man is taken by the family to the emergency department because he has decreased consciousness, and the body suddenly stiffens. Patients begin to experience changes in behavior in the form of difficulty sleeping, when invited to talk quietly, laughing alone, and whispering without the other person. TORCH examination found an increase in anti-toxoplasma IgM and IgG. This patient is then given basic life support in the form of ABC (airway, breathing, circulation support) and seizure management. Also given risperidone 2 mg / 12 hours, pyrimethamine 1-II (1x200 mg), pyrimethamine day III-XXI (1x 25 mg), intravenous Cefotaxime 2g / 8 hours, Clindamycin 500 mg / 8 hours. The patient experienced improvement after the second week of treatment. Conclusion: Toxoplasmosis causes lesions in the brain that cause changes in brain neurotransmitter pathways, which lead to changes in patient behavior.